Purification and crystallographic studies of a putative carbohydrate‐binding module from the Ruminococcus flavefaciens FD‐1 endoglucanase Cel5A. Issue 8 (1st August 2015) - Pires, Ana José; Ribeiro, Teresa; Thompson, Andrew; Venditto, Immacolata; Fernandes, Vânia O.; Bule, Pedro; Santos, Helena; Alves, Victor D.; Pires, Virginia; Ferreira, Luis M. A.; Fontes, Carlos M. G. A.; Najmudin, Shabir
<x xml:space="preserve">Abstract</x> Ruminant herbivores meet their carbon and energy requirements from a symbiotic relationship with cellulosome‐producing anaerobic bacteria that efficiently degrade plant cell‐wall polysaccharides. The assembly of carbohydrate‐active enzymes (CAZymes) into cellulosomes enhances protein stability and enzyme synergistic interactions. Cellulosomes comprise diverse CAZymes displaying a modular architecture in which a catalytic domain is connected, via linker sequences, to one or more noncatalytic carbohydrate‐binding modules (CBMs). CBMs direct the appended catalytic modules to their target substrates, thus facilitating catalysis. The genome of the ruminal cellulolytic bacterium Ruminococcus flavefaciens strain FD‐1 contains over 200 modular proteins containing the cellulosomal signature dockerin module. One of these is an endoglucanase Cel5A comprising two family 5 glycoside hydrolase catalytic modules (GH5) flanking an unclassified CBM (termed CBM‐Rf2) and a C‐terminal dockerin. This novel CBM‐Rf2 has been purified and crystallized, and data from cacodylate‐derivative crystals were processed to 1.02 and 1.29 Å resolution. The crystals belonged to the orthorhombic space group P212121. The CBM‐Rf2 structure was solved by a single‐wavelength anomalous dispersion experiment at the As edge.